Resting state functional connectivities that mediate the association between anxiety and sleep in elderly - Ling, Genevieve Tek Ting (Nanyang Technological University, 2023)
Elderly individuals often suffer from comorbid anxiety and sleep disturbances, which hinder healthy ageing and contribute to cognitive decline. Although neuroimaging has demonstrated regions associated with anxiety and sleep in individuals, few studies have analysed the convergence of anxiety and sleep disturbances in elderly through the perspective of resting-state functional connectivity. Therefore, this study aims to investigate the association between anxiety and sleep in elderly, as well as elucidate the functional connectivities that mediate this association. 256 elderly participants completed a magnetic resonance imaging scan, in addition to psychometric assessments on anxiety severity and subjective sleep quality. Correlation analysis, network-based statistics and brain mediation analysis were performed in RStudio. Anxiety symptoms were positively associated with sleep disturbances, while resting-state functional connectivity was revealed to partially mediate the anxiety-sleep relationship. Overall, the findings of this study indicate network-specific functional connectivities that mediate the association between anxiety and sleep in elderly, while addressing future directions for research and therapeutic interventions.